A responsibility to commercialize? Tracing academic researchers' evolving engagement with the commercialization of biomedical research. Issue 3 (2nd September 2019) - Holloway, Kelly; Herder, Matthew
ABSTRACT: Governments and academic institutions have embraced the importance of commercializing research through the late twentieth century. In this study, we seek to understand scientists' contemporary understanding of the role of academic science in this commercially oriented environment. We present findings based on 30 semi-structured interviews with biomedical researchers from different career stages at a medium-sized university in Canada about patenting, presenting at conferences, creating a company, applying for funding, and interacting with industry. We attend to differences between 'established' researchers (faculty) and 'emerging' researchers (graduate students and post-doctoral fellows). In general, all participants indicated that commercialization is a normal and mundane aspect of university research. They communicate a considerable amount of ambivalence about commercializing their biomedical research, but stress that the pressure to do so is beyond their control. There was a consensus among most participants that commercialization is the only way to bring innovations in biomedical research to patients; further, it was a responsibility.